2013
DOI: 10.1177/105678791302200101
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Ontario Teachers’ and Students’ Perceptions of Large-Scale Reform

Abstract: Within the following text, educational reform is examined to reveal how and to what extent Ontario secondary teachers (n = 87) have implemented educational changes that had a direct impact on students (n = 396), themselves, and curriculum. Our mixed methods data, while limited in scope, indicated that secondary school teachers were largely content with in-service professional development, resource supplies, and leadership. These new outcomes marked a swing away from the discontent noted in research completed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
2
6
1
Order By: Relevance
“…Some sample teachers had difficulty changing former teaching praxes (teacher-directed lessons) and student evaluation modes (tests and exams) to student-centered strategies, integration of technology, and performance or authentic assessment. In contrast to the previous reform studies in Canada (Joong & Ryan, 2013; Ryan & Joong, 2005) and Sierra Leone (Joong & Noel, 2013), sample teachers in the Philippines indicated that there was adequate support in terms of resources but not for in-service training. Brooks and Sutherland (2014) had similar findings in their survey of secondary school principals in the Philippines.…”
Section: Conclusion and Discussion On Research Questionscontrasting
confidence: 87%
See 4 more Smart Citations
“…Some sample teachers had difficulty changing former teaching praxes (teacher-directed lessons) and student evaluation modes (tests and exams) to student-centered strategies, integration of technology, and performance or authentic assessment. In contrast to the previous reform studies in Canada (Joong & Ryan, 2013; Ryan & Joong, 2005) and Sierra Leone (Joong & Noel, 2013), sample teachers in the Philippines indicated that there was adequate support in terms of resources but not for in-service training. Brooks and Sutherland (2014) had similar findings in their survey of secondary school principals in the Philippines.…”
Section: Conclusion and Discussion On Research Questionscontrasting
confidence: 87%
“…In our class observations, a few schools do provide special education services such as special education teachers, reading classes, behavioral classes, remedial classes, and/or alternative programs. Results are similar to the integration of students with special needs programs in our Canada and China Reform studies (Joong, 2012; Joong & Ryan, 2013; Ryan & Joong, 2005).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations